An experimental investigation on the effect of incorporating graphene nanoplatelets on the low-velocity impact behavior of fiber metal laminates. (October 2021) - Fathi, Azadeh; Liaghat, Gholamhossein; Sabouri, Hadi
Abstract: In this study, experimental investigations are implemented to evaluate the effect of incorporation of graphene nanoplatelets (GNPs) on the low-velocity impact behavior of composites and fiber metal laminates (FMLs). The hand layup technique is employed to fabricate composite specimens and FML panels with 2/1 configuration. Impact response and damage patterns of unmodified and modified specimens subjected to various impact energy levels are compared. The results reveal that the incorporating 0.2 wt% of GNPs strengthens the impact resistance of FMLs so that the modified panels possess higher bending stiffness, peak load, energy absorption and SEA compared to the unreinforced ones. Visual inspections and SEM images exhibit that the inclusion of GNPs enhances the adhesion between resin/fibers as well as composite plies, thereby reducing damage area and increasing penetration threshold of FMLs. In addition, reinforcing composite panels considerably improves the impact behavior in comparison with the unmodified composites. Highlights: The effect of adding GNPs on impact response of composites and FMLs is investigated. The behavior of FMLs subjected to impact and quasi-static loading is compared. The addition of GNPs to FML panels increases the perforation threshold. Reinforced FMLs experience the less damage extent under different impact energies. Modified composites possess higher impact resistance compared to unmodified ones.